Nusselt number and friction factor correlation of solar air heater having twisted-rib roughness on absorber plate. (January 2019) - Kumar, Anup; Layek, Apurba
Abstract: A study is carried out providing integrated roughness over absorber plate of solar air heater to improve its potential for heat transfer augmentation. A number of experiments are conducted with twisted roughness to pursuit test results for heat transfer augmentation along with friction factor phenomena. The experiments stand with a relevant range of flow parameters as Reynolds number from 3500 to 21000, and geometric parameters such as relative roughness pitch from 6 to 10, rib inclination angle domain from 30° to 90° and twist ratio from 3 to 7. Finally, the correlations are developed for the Nusselt number and the friction factor in terms of flow parameter and roughness geometries and compared with experimental results which are reasonable and eventually satisfactory. The enhancement of heat transfer as well as friction factor are obtained and compared with smooth conventional duct for the same flow circumstances. The results are analyzed to pursuit optimum condition of roughness parameters to achieve the best performance. Highlights: The novel twist rib is encapsulated as roughness over absorber plate in solar air heater. The Liquid crystal thermography technique is used to determine plate temperature. The effect of geometric parameters is experimentally investigated for twisted rib. Correlation is developed for Nusselt number and Friction factor. Optimal values for geometric parameters are obtained for which the Nusselt number is maximum.